2004
DOI: 10.1093/jac/dkh158
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of fosfomycin in the cerebrospinal fluid of neurointensive care patients with ventriculostomy-associated ventriculitis

Abstract: The present pharmacokinetic study indicates that 8 g of fosfomycin three times per day should provide sufficient antimicrobial concentrations in the CSF for the overall treatment period. Thus, the co-administration of fosfomycin could be useful for the treatment of ventriculitis caused by susceptible pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 27 publications
4
91
1
3
Order By: Relevance
“…In this respect, some studies have found that fosfomycin demonstrates concentration-dependent killing activity against strains of Escherichia coli and Proteus mirabilis in vitro as well as strains of S. pneumoniae in vivo [38,39]. However, other studies have noted timedependent bactericidal activity of fosfomycin against S. aureus strains in vitro [32,40].…”
Section: Pharmacodynamic Characteristics Of Fosfomycinmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, some studies have found that fosfomycin demonstrates concentration-dependent killing activity against strains of Escherichia coli and Proteus mirabilis in vitro as well as strains of S. pneumoniae in vivo [38,39]. However, other studies have noted timedependent bactericidal activity of fosfomycin against S. aureus strains in vitro [32,40].…”
Section: Pharmacodynamic Characteristics Of Fosfomycinmentioning
confidence: 99%
“…In patients with ventriculostomy-associated ventriculitis who received 8 g of i.v. fosfomycin three times daily, the CSF-to-serum fosfomycin AUC ratio has been found to be 27% at steady state [32]. Fosfomycin has also been shown to achieve clinically relevant drug concentrations in the brain parenchyma [29].…”
Section: Central Nervous System (Cns) Infectionsmentioning
confidence: 99%
“…A cumulative effect is observed after multiple doses. 31,43 The main pharmacokinetic parameters are presented in Table 1. Serum protein binding is estimated at below 3%, which allows a large tissue availability.…”
Section: Pharmacokinetics Of Intravenous Fosfomycinmentioning
confidence: 99%
“…Impairment of hepatic function has little impact on the plasma elimination half-life of fosfomycin. 44 In spite of 40 years of evolution of methods to determine fosfomycin concentrations, there has been almost no progress in lowering the limit of sensitivity of the assays, which is approximately 1 mg/L by gas chromatography 43,49,50 or by capillary gas chromatography, 51,52 while by microbiological methods, it is reported to be 0.7-1.5 mg/L when mentioned. 47,48,53,54 …”
Section: Pharmacokinetics Of Intravenous Fosfomycinmentioning
confidence: 99%
See 1 more Smart Citation